2011
DOI: 10.1071/wf09120
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires and the Canadian Forest Fire Weather Index system for the Daxing'anling region of China

Abstract: The Canadian Forest Fire Weather Index (FWI) system was evaluated for the Daxing'anling region of northern China for the 1987-2006 fire seasons. The FWI system reflected the regional fire danger and could be effectively used there in wildfire management. The various FWI system components were classified into classes (i.e. low to extreme) for fire conditions found in the region. A total of 81.1% of the fires occurred in the high, very high and extreme fire danger classes, in which 73.9% of the fires occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 12 publications
4
29
0
2
Order By: Relevance
“…Nogueira et al () report moderate to strong correlations between several fire danger indices, including FWI and FFDI, and monthly BA for four biomes in Brazil. Tian et al () however, found that FWI, or the FFMC, explained only a small fraction of variation in BA in forests of the Daxing'anling region of northern China. Clearly, there is substantial regional variation in the response of BA or other fire activity metrics to the common fire danger indices, potentially causing confusion and uncertainty among fire management agencies and the public about the practical meaning of the different fire danger categories.…”
Section: Forest Fire Hazard Prediction For Risk Mitigationmentioning
confidence: 99%
“…Nogueira et al () report moderate to strong correlations between several fire danger indices, including FWI and FFDI, and monthly BA for four biomes in Brazil. Tian et al () however, found that FWI, or the FFMC, explained only a small fraction of variation in BA in forests of the Daxing'anling region of northern China. Clearly, there is substantial regional variation in the response of BA or other fire activity metrics to the common fire danger indices, potentially causing confusion and uncertainty among fire management agencies and the public about the practical meaning of the different fire danger categories.…”
Section: Forest Fire Hazard Prediction For Risk Mitigationmentioning
confidence: 99%
“…We found for this region that when FFMC > 85, conditions are critical for fire initiation and spread. Values of FFMC = 75 (Cheney and Sullivan, 2008), FFMC = 81-83.3 (De Groot et al, 2005), FFMC > 82 (Amiro et al, 2004) and FFMC ≥ 85 (Tian et al, 2011) were defined in other ecosystems as thresholds for fire spread. The FFMC value corresponding to the upper-limit of the lower category defined for the fire danger scale can be related with the results of Dentoni et al, (2006), who analyzed a total of 1882 hot-spots occurred during eleven seasons (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) in the Andean Patagonian ecosystems.…”
Section: Surface Dead Fuels Ignition In Native Patagonian Forests 135mentioning
confidence: 99%
“…However, dead fuels gain and lose water according to the same physical principles, and fire behavior respond in the same way all over the world to variations in fuel conditions, weather, and topography (Taylor and Alexander, 2006). These facts made that these moisture codes were adapted, used, and successfully implemented as relative indicators of fuel moisture in many different ecosystems throughout the world, such as in Canada, USA, New Zealand, Indonesia, Malaysia, China, Mexico, Portugal, and various other countries of southern Europe (Alexander and Cole, 2001;Raínha and Fernandes, 2002;Taylor and Alexander, 2006;De Groot et al, 2006;Tian et al, 2011).…”
mentioning
confidence: 99%
“…As such, the annual burned forest area within this region ranks the first in all of China, making it the most serious forest fire hazard area in the country. Taking records in the 20 years from 1987 to 2006 as examples (Tian et al 2011 ), 1059 fires occurred in this period, with a total burned area of 2.81 £ 10 6 ha, including 1.36 £ 10 6 ha of forest area. Tian and colleagues (2011) further indicated that, on average, each fire burned an area of 2660 ha, 1324 ha of which was ever covered by forest.…”
Section: Introductionmentioning
confidence: 99%